An unusual case of pulmonary embolism following ayurveda massage therapy - Adiody, Supriya; Narayanan, Vishnu; Abraham, Nikhila (International Journal Of Community Medicine And Public Health, 2025)
Ayurvedic treatments, including traditional massage therapies, are widely used for their holistic health benefits. However, improper techniques may pose serious health risks. We present the case of a 59-year-old female with diabetes, dyslipidemia, and hypertension who developed a massive pulmonary embolism (PE) following a month-long Ayurvedic lower leg massage for varicose veins. She presented with exertional dyspnea and had a history of prolonged immobilization. Clinical evaluation, elevated D-dimer levels, echocardiography findings of right ventricular dysfunction, and CT pulmonary angiography confirming bilateral pulmonary artery thrombi led to the diagnosis of PE. She was managed with oxygen therapy and anticoagulation, transitioning from low-molecular-weight heparin to direct oral anticoagulants. The patient showed clinical improvement and was discharged on anticoagulation therapy. This case highlights the rare but significant risk of venous thromboembolism (VTE) following deep tissue massage, likely due to endothelial damage and venous stasis. It underscores the importance of careful patient evaluation before engaging in alternative therapies, particularly in individuals with predisposing risk factors. Raising awareness among practitioners and patients regarding the potential cardiovascular risks of unregulated Ayurvedic treatments is crucial for preventing such adverse events.